Penerapan Pasal 24 Ayat (1) Huruf C Undang-Undang Nomor 12 Tahun 2022 Terkait Barang Bukti Dalam Penegakan Hukum Tindak Pidana Kekerasan Seksual Di Wilayah Hukum Polda Jawa Barat - Sania Trinanti; Somawijaya Somawijaya; Agus Takariawan (WELFARE STATE Jurnal Hukum, 2026)
This study examines the implementation of Article 24 Paragraph (1) Letter c of Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS), with a specific focus on its application within the jurisdiction of the West Java Regional Police (Polda Jawa Barat). The research concentrates on the challenges faced in law enforcement, particularly in the process of collecting and validating evidence in sexual violence cases. Although the legal framework clearly permits the use of non-physical evidence, such as victim testimony, psychological assessments, and digital recordings, its practical application remains problematic. Many cases occur in private spaces without witnesses, making it difficult for investigators to obtain concrete supporting evidence. Additionally, strong social stigma and the fear of victim-blaming discourage timely reporting, further complicating investigations. The study finds that limited training and the lack of specialized skills among police officers hinder effective case handling. Therefore, the study recommends strengthening investigator capacity and adopting a more victim-centered, trauma-informed approach to improve justice outcomes in sexual violence cases.